The development of the oral communication in A1 learners through picture description strategy in inglish classes - Infante Vera, Alba Edelmira (2023)
This study intends to explore and understand the A1 level English learners’ perspectives about the use of picture description strategy for improving the oral communication in EFL classes at Teodoro Wolf public high school located in the Province of Santa Elena., Ecuador. The study was conducted using a qualitative method to gather data through interviews with 28 participants of 9 Year EGB. Classroom ’B’ who were chosen by convenience. A questionnaire with 5 open questions were applied to know the learners’ perceptions about the use of picture description strategy in EFL classes. The findings revealed that the majority of A1 learners have a positive perception of the picture description strategy, as it helps them to improve their oral communication skill. Participants also found that the use of visual aids is an effective resource to make language learning a more pleasant experience, stimulating the imagination, and promoting speaking skill. Also, the results suggest that the lack of confidence at the moment to communicating in English is a common issue among EFL learners. EFL learners often feel embarrassed or afraid of being judged when speaking in front of others. This fear can lead to anxiety and affect their ability to communicate effectively. Teachers can supply opportunities to practice speaking regularly, create a supportive and encouraging environment that allows learners to make mistakes and provide proper feedback. Further research is needed to investigate the impact of PDS on other language skills and to explore its potential for different age groups and contexts.